Pengaruh Store Atmosphere, Price dan Service Quality terhadap Minat Beli Konsumen Pada Cooffee Shop Kopi - Asrul (Jurnal Informatika Ekonomi Bisnis, 2023)
This type of research is descriptive and quantitative research, because this research is used to provide an objective description or description of a situation. This study aims to see the effect of Store Atmosphere on Purchase Intention, the effect of Price on Purchase Intention, the effect of Service Quality on Purchase Intention and see the effect of Store Atmosphere, price, Service Quality on purchase intention. This research was conducted in the form of interviews and distributing questionnaires. The population in this study were all consumers who had made a purchase at least once at a coffee coffee shop from the heart of Pariaman City. The sample in this study were 49 respondents, the sampling technique used incidental sampling or sampling technique based on chance. This study uses hypothesis testing, the results of this study indicate that partially Store Atmosphere does not have a significant effect on purchase intention because the value of ttab>thit (1.6772> 0.174), price has a significant effect on purchase intention because ttab<thit (1.6772<13.906 ) and service quality have a significant effect on purchase intention because ttab<thit (1.6772<3.573). While simultaneously Store Atmosphere, price, service quality have a significant effect on purchase intention because fhit>ftab (156.543 > 1.6772). Based on the results of the Determination test (R2), it was found that the contribution of the independent variables Store Atmosphere (X1), price (X2), and service quality (X3) to purchase intention (Y) was 91.3%, this shows that the influence between the variables is very high. strong because the greater the Rsquare number the stronger the influence between these variables.